Aktivitas Senyawa Sargassum sp. sebagai Anti-aterosklerosis dengan Pembandingan Ligan-Reseptor HMG-CoA Reduktase- Simvastatin (1HW9) dan Uji Toksisitas secara In-Silico - Sarah Zaidan; Syamsudin Abdillah; Deni Rahmat; Ratna Djamil; Esti Mumpuni (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Introduction:Sargassum.sp is one of the marine biota published as antiaterosclerosis, but compound toxicity data need to be explored for safety. Method: Virtual screening has been done with MVD software from active compounds contained in sargassum where has activity as antiaterosclerosis with the mechanism of hypolipidemic effects. Test compounds in sargassum include: fucoidan, rhamnose, fucose, galactose, fucoxantin, alginate, phlorofucofuroeckol A, phloroglucinol, phlorotannin, with HMG-COA Reductase-Simvastatin adenosine receptors with a 1HW9 /PDB code. Its toxicity is predicted using pkCSM (online). Results: The value RS, RMSD value as a result of the docking simulation carried out on said compounds, the following results are obtained: fucoidan (-110,420; 1,478), rhamnose (-72,081; 1,629), fucose (-98,408; 1,546), galactose (-95,757; 5,187), fucoxantin (-106,297; 2,161), alginate (-84,674; 2,897), phlorofucofuroeckol A (-106.701; 2,809), phloroglucinol (-103,140; 2,142), phlorotannin (-48,826; 7,750). The prediction results of toxicity showed fucoidan, rhamnose, fucose, galactose, fucoxantin, alginate, phlorofucofuroeckol A, phloroglucinol and phlorotannin not toxic with LD50 0.95-2.482g / kg. Conclusion:Based on RS values, fucoidan, fucoxantin and phlorofucofuroeckol A compounds contained in brown seaweed were predicted to have activity as antiaterosclerosis. Compounds in brown seaweed can also be predicted to be relatively non-toxic with a value of LD50 0.95-2.482g / kg.